The Character of Purulent-Inflammatory Diseases of The Retroperitoneal Region - Matmurotov K.J; Kuchkarov A.A (Zien Journals, 2023)
Conducted a retrospective data analysis of 439 patient records with purulent-inflammatory diseases of the retroperitoneal space, receiving inpatient treatment in the department of purulent surgery of the multidisciplinary clinic of the Tashkent Medical Academy from 2010 to 2022, in order to select the observation group.All patients, along with general clinical laboratory studies, underwent MSCT and ultrasound of the retroperitoneal region before the start of the treatment complex to determine the operational tactics of treatment. At the same time, a limited pathological focus (abscess) was detected in 28.7% of cases, signs of phlegmon were noted in 51.4% of cases, and combined types or postoperative fistulas were observed in 19.9% of cases.
Keywords: observed; analysis; ultrasound; postoperative